The British shipbuilding industry, 1870-1914 - Pollard, Sidney (Harvard Univ. Press, 1979)
This book thus provides rich information on how the businessmen in charge of these enterprises adopted new forms of technology-changes that involved the transformation of the theory and practice of naval architecture and marine engineering. It delineates ways in which the en- trepreneurs defined their relations with their suppliers and with their customers, both private and public. The latter were...